Using 3D Microscopy to Analyze Experimental Cut Marks on Animal Bones Produced with Different Stone Tools - Erika Moretti; Simona Arrighi; Francesco Boschin; Jacopo Crezzini; Daniele Aureli; Annamaria Ronchitelli (Ethnobiology Letters, 2015)
This study uses a combination of digital microscopic analysis and experimental archaeology to assess stone tool cut marks on animal bones. We used two un-retouched flint flakes and two burins to inflict cut marks on fresh, boiled, and dry ungulate  bones. The experiment produced three series of three engravings on each bone with each of the experimental tools. The first series involved one single stroke; the second, two strokes in the same direction; and the third, multiple strokes using a to-and-fro movement. We analyzed the striations using a Hirox 3D digital microscope (KH-7700) and collected metric and profile data on the morphology of the cut marks. In order to describe the shape of each cross section, we calculated the ratio between the breadth at the top and the breadth at the floor of cut marks. Preliminary results show that both the tool type and the method of creating the cut mark influence the shape of the resulting groove. In our experiment, morphological parameters can be used to differentiate between marks produced using un-retouched flint flakes and those produced using burins. However, neither morphological nor morphometric analysis allows us to identify the mechanical motion used to produce the cuts, nor the state of the bone (fresh, boiled, or dry) at the moment of marking.